PENGARUH MOTIVASI INTRINSIK TERHADAP HASIL BELAJAR EKONOMI SISWA - Rijal, Syarifah, Samio (FKIP UMN ALWASHLIYAH, 2024)
The purpose of this study was to determine the effect of intrinsic motivation on the learning outcomes of students in economic education. The population of the study was all 60 students in grade XII of SMA Swasta Nurul Hasanah Tembung consisting of 2 parallel classes. The number of samples determined in this study was 60 students consisting of class XI-1 = 30 people and X-2 IPS = 30 people, which were taken in total (total sampling). The tools used to collect data in this study were Observation, Questionnaires. From the results obtained a correlation value of 0.256, while the correlation value in the correlation table (For N = 60 and significance level = 0.05) obtained a value of 0.250. While the magnitude of the correlation value of the calculation results (t) is 2.015 While the magnitude of the value (t) in the table is 1.67 for V = 60 and significant 95% (t = 0.95). Thus, the hypothesis that has been set can be accepted as true because the value of t(count) > t(table) or 2.015 > 1.67, meaning that the hypothesis that states